PEWARISAN NILAI SEJARAH LOKAL (TERNATE) SEBAGAI SUMBER BELAJAR DI SMA NEGERI 6 TERNATE PROVINSI MALUKU UTARA - Zulkifli Zulkifli; Leny MS Tomagola (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This study aims to identify and describe the role of history teachers in utilizing local historical values ​​as learning resources at State Senior High School 6, Ternate City, North Maluku Province. The researchers used a descriptive qualitative approach, with history teachers and students as subjects. Data collection techniques included observation, interviews, and documentation. The results indicate that history teachers have not fully utilized local historical sources as learning resources for history subjects due to the limited availability of local historical sources, a challenge that has been a challenge. Therefore, the results of this study serve as a basis for a collaborative evaluation to improve local historical sources and effectively address the challenges faced by history teachers. The application of local historical values ​​as learning resources is crucial, enabling students to understand local historical records, from the arrival of Islam in Ternate to the arrival of Europeans who came to trade spices and sought to control Ternate.